1978
DOI: 10.1007/bf02013262
|View full text |Cite
|
Sign up to set email alerts
|

Effects produced by the administration of high doses of 1,25-dihydroxycholecalciferol to the chick embryo

Abstract: White Leghorn chick embryos were injected on the 15th day of incubation with 70 to 300 pmoles 1,25-(OH)2D3. All doses produced hypercalcemia; with the highest dose, the concentration of calcium in serum started to rise 4 h after the injection, reached a peak 20 h after, and was still high 48 h after. Twenty hours after the injection of the same dose, the concentration of inorganic phosphorus in the serum was significantly lower than in the corresponding controls. The tibias from 17-day-old chick embryos inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Narbaitz and Tolnai [1978] showed that the injection of 1,25-DHCC into chick embryos produces hypercalcemia and sug gested that this results from an increase in the resorption of calcium through the chorioallantoic membrane. In support of this suggestion, Narbaitz et al [1980] dem onstrated the presence of receptor cells for 1.25-DHCC in the choriollantois and Nar baitz et al [1981a] showed that the hormone is capable of increasing carbonic anhydrase activity in the membrane; this enzyme is responsible, at least in part, for the solubili zation of the shell mineral.…”
Section: Discussionmentioning
confidence: 99%
“…Narbaitz and Tolnai [1978] showed that the injection of 1,25-DHCC into chick embryos produces hypercalcemia and sug gested that this results from an increase in the resorption of calcium through the chorioallantoic membrane. In support of this suggestion, Narbaitz et al [1980] dem onstrated the presence of receptor cells for 1.25-DHCC in the choriollantois and Nar baitz et al [1981a] showed that the hormone is capable of increasing carbonic anhydrase activity in the membrane; this enzyme is responsible, at least in part, for the solubili zation of the shell mineral.…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes have been observed in young chicks [17]. Narbaitz and Tolnai [8] have shown that the injection of 1,25(OH)2D 3 to chick embryos on the 15th day of incubation produces hypercalcemia but that this is accompanied by hypophosphatemia rather than hyperphosphatemia. Our present results confirm this observation and show that similar response can be obtained as early as the 9th day of incubation.…”
Section: Discussionmentioning
confidence: 54%
“…A first series of experiments was carried out to find out if the peripheral rim of unmineralized (osteoid) trabeculae which had been described previously [8] in the bones from embryos injected with 1,25(OH)zD 3 on the 15th day of incubation could also be induced at earlier ages. These experiments showed that the characteristic bone changes could be induced only when 1,25(OH)2D 3 was injected on the 1 lth day of incubation or later.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations